Investigation and management of anaemia. (April 2021) - Hayter, Joanne; Thomas, Alison
Abstract: The average lifespan of an erythrocyte is 120 days, and maintenance of a normal haemoglobin requires the rate of production of erythroid cells to match the rate of loss from the circulation. Where this is insufficient, anaemia ensues. Deficiency of haematinics (iron, vitamin B12, folate), bone marrow infiltration or chronic inflammation and organ dysfunction can all result in impaired erythropoiesis. Abnormalities of the erythroid membrane, globin chains or intracellular enzymes shorten red cell lifespan, resulting in a congenital haemolytic anaemia. Acquired haemolysis is commonly immune or microangiopathic in aetiology. A detailed history including dietary, drug and family history, followed by interpretation of the full blood count, examination of the blood film and appropriate interpretation of simple tests (e.g. vitamin B12, folate, ferritin), often identifies the cause of the anaemia. Older patients and those with complex co-morbidities can have multiple factors contributing to their anaemia. Management of anaemia is primarily focused on treating the underlying cause. Blood transfusion is reserved for cases of acute-onset symptomatic anaemia and cases of anaemia with no remedial cause.